2020
DOI: 10.4314/ijma.v2i14.5
|View full text |Cite
|
Sign up to set email alerts
|

The Iberian-Guanche rock inscriptions at La Palma Is.: all seven Canary Islands (Spain) harbour these scripts

Abstract: Rock Iberian-Guanche inscriptions have been found in all Canary Islands including La Palma: they consist of incise (with few exceptions) lineal scripts which have been done by using the Iberian semi-syllabary that was used in Iberia and France during the 1st millennium BC until few centuries AD .This confirms First Canarian Inhabitants navigation among Islands. In this paper we analyze three of these rock inscriptions found in westernmost La Palma Island: hypotheses of transcription and translation show that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 11 publications
2
11
0
1
Order By: Relevance
“…It is also supported by rock geometrical-incised signs in Blombos and Klasier River Caves, and Howiesons Poort complex rocks or pieces found in South Africa and dated, 60,000 -100,000 years BC (Henshilwood & Dubreuil 2011;Henshilwood & D´Errico 2011;Texier et al 2010). Some of these latter signs are similar to those described by us on the Rock of the Dead in Tenerife, Barranco de Ruiz, San Juan de la Rambla, Canary Islands (Arnaiz-Villena et al 2019a) or at La Palma Island (Arnaiz-Villena et al 2020a); and also to those other incise/lineal rock scripts found at all other Canary Islands (Arnaiz-Villena et al 2015;2019b;Benito-Mateo et al 2016;de Balbín-Behrmann et al 2009;del Arco-Aguilar et al 2009;González-Antón et al 1995;2016;Asociación sociocultural Archinife 2016).…”
Section: Prehistoric Scripts and The Lineal Megalithic Rock Scriptssupporting
confidence: 86%
“…It is also supported by rock geometrical-incised signs in Blombos and Klasier River Caves, and Howiesons Poort complex rocks or pieces found in South Africa and dated, 60,000 -100,000 years BC (Henshilwood & Dubreuil 2011;Henshilwood & D´Errico 2011;Texier et al 2010). Some of these latter signs are similar to those described by us on the Rock of the Dead in Tenerife, Barranco de Ruiz, San Juan de la Rambla, Canary Islands (Arnaiz-Villena et al 2019a) or at La Palma Island (Arnaiz-Villena et al 2020a); and also to those other incise/lineal rock scripts found at all other Canary Islands (Arnaiz-Villena et al 2015;2019b;Benito-Mateo et al 2016;de Balbín-Behrmann et al 2009;del Arco-Aguilar et al 2009;González-Antón et al 1995;2016;Asociación sociocultural Archinife 2016).…”
Section: Prehistoric Scripts and The Lineal Megalithic Rock Scriptssupporting
confidence: 86%
“…This is particularly evident with the many small Canarian fat "goddesses" statues and/or figurines which are similar to those found by Gimbutas (6,000 -3,000 years BC) and in Mediterranean Iberia: scholars name this influence on Canarian culture "The Gibraltar Strait Circle" that includes Mediterranean, Europe and Africa (González-Antón et al 2016). We also add a similarity with singular Malta Archipelago culture: "fat goddesses", extant cart-ruts in both Canarian and Malta Archipelagos 2019a;2020a;2020b;2020c;Medina and Arnaiz-Villena 2018a;2018b). Some Iberian scholars have not studied Canary Islands Ibero-Guanche scripts because of "lack of enough material" (Arnaiz-Villena, personal talk to scholars); however, Italian lineal languages (Fig.…”
Section: Ti-m Missaou/shelter Inscriptionsmentioning
confidence: 99%
“…Arnaiz-Villena & Alonso- García 2001;Arnaiz-Villena et al 2019b;2020a;2020b).…”
Section: Ti-m Missaou/shelter Inscriptionsunclassified
“…Part of Saharan climate displaced people are proposed to have reached Canary Islands where common rock Ibero-Guanche and older lineal scripts are found (Arnaiz-Villena et al 2019a;2020a;2020b) Volcanic rock environment had to be taken by people for any socio-cultural archaeologic manifestation. However, megalithic constructions (Zonzamas rock carved calendar and Cart-ruts in Lanzarote) are found.…”
Section: Canary Islandsmentioning
confidence: 99%
“…Also, pyramids have been reported in all Islands. Thus, navigation among Islands existed (Arnaiz-Villena et al 2019a;2020a;2020b;Mederos-Martín & Escribano-Cobo 2005). Other rock calendars have been described in Canary Islands and multiple prehistoric artifacts have been found, like "fat" goddesses similar to those found by Gimbutas in Europe older than 3,500 years BC: at La Fortaleza (Gran Canaria), Tara (Telde, Gran Canaria) (Arco-Aguilar & Navarro-Mederos 1996;Arnaiz-Villena et al 2020a).The fact that ancient Canarians or Guanches have resisted Phoenician, Roman, Arab and other invasions led to French-Spanish conquerors to find some of this Guanche ancient art/folk manifestations without much alteration including rock paintings and rock scripts of both Iberian and Lybic characters and also more ancient Megalithic Lineal Scripts (Vazquez-Hoys 2008;Muñoz-Gambero 2019).…”
Section: Canary Islandsmentioning
confidence: 99%